2016
DOI: 10.1177/1367877916674751
|View full text |Cite
|
Sign up to set email alerts
|

Immersion, authenticity and the theme park as social space: Experiencing the Wizarding World of Harry Potter

Abstract: This article examines the visitor experience of the Wizarding World of Harry Potter (WWOHP) theme park at Universal Studios Orlando. The park is hugely popular and has been embraced by the series’ devoted but critical fanbase. Prior research on theme parks has generally focused on critiques of their form, leading to a limited understanding of their appeal. This article asks how fan-visitors interpret this simulated environment, and what leads them to embrace it. It does this with an ethnographic approach, util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 21 publications
1
45
0
1
Order By: Relevance
“…Popular culture and the future of tourism Popular culture related travel thus holds special meaning to those who consider themselves fans, and travel provides them with two opportunities: One is an immersion in the often fictional world depicted on screen or in books (Waysdorf and Reijnders, 2016), the other consists of face-toface interactions with other fans, transferring the fandom community from digital to physical contexts (Kington, 2015). Although Croy (2018) points out that only a small percentage of, for example, film tourists consider themselves deeply involved fans, for these travelers it is the community building and subsequent sense of belonging and membership that lies at the core of their activities (Reichenberger and Smith, 2019).…”
Section: The Popularity Of Popular Culturementioning
confidence: 99%
“…Popular culture and the future of tourism Popular culture related travel thus holds special meaning to those who consider themselves fans, and travel provides them with two opportunities: One is an immersion in the often fictional world depicted on screen or in books (Waysdorf and Reijnders, 2016), the other consists of face-toface interactions with other fans, transferring the fandom community from digital to physical contexts (Kington, 2015). Although Croy (2018) points out that only a small percentage of, for example, film tourists consider themselves deeply involved fans, for these travelers it is the community building and subsequent sense of belonging and membership that lies at the core of their activities (Reichenberger and Smith, 2019).…”
Section: The Popularity Of Popular Culturementioning
confidence: 99%
“…Prior research identified that spirit can be considered a result of publicly displayed membership. For example, participation in public discussions and panels (Kington, 2015; Larsen and Zubernis, 2011), the writing of fan fiction (Hellekson and Busse, 2006; Pearson, 2010) as well as cosplay (costume play; Anderson, 2014; Lamerichs, 2010; Waysdorf and Reijnders, 2016) help to visibly communicate fandom membership and contribute to a differentiation between less and more involved individuals. Partaking in these activities can be considered a form of serious leisure as they require effort in the form of knowledge and commitment and perseverance to achieve.…”
Section: Fan-based Community Buildingmentioning
confidence: 99%
“…Although some of this research takes place within tourism spaces, it frequently does not sufficiently acknowledge tourism’s nature and contribution (e.g. Kruse, 2005; Toy, 2017; Waysdorf and Reijnders, 2016). This diversity results in a body of literature that often appears fragmented in both its focus and its theoretical and disciplinary groundings (Gyimóthy et al, 2015), making it challenging for tourism research and industry to explore fandoms and their unique characteristics in tourism spaces such as destinations, activities, attractions or events (Roberson and Grady, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(Waysdorf and Reijnders 2018, 183). By taking a themed space derived from an intellectual media property on its own terms and exploring audience responses, Waysdorf and Reijnders (2018) Equating physical experiences with virtual equivalents may seem objectionable due to the deep-rooted association between tourism and physical embodiment highlighted in the previous section (also Hills 2016;2017, 214). In contrast, theories of 'post-tourism' have started addressing how technologies such as the Internet have meant that travellers 'do not have to leave their houses in order to see the objects-to-be-seen' (Heitmann 2011, 55).…”
Section: However Writing On the Wizarding World Of Harry Potter At Umentioning
confidence: 99%